2010
DOI: 10.2183/pjab.86.202
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric hydrogenation of ketones: Tactics to achieve high reactivity, enantioselectivity, and wide scope

Abstract: Ru complexes with chiral diphosphines and amine-based ligands achieve high catalytic activity and enantioselectivity for the hydrogenation of ketones under neutral to slightly basic conditions. The chiral environment is controllable by changing the combination of these two ligands. A concerted six-membered transition state is proposed to be the origin of the high reactivity. The η6-arene/TsDPEN–Ru and MsDPEN–Cp*Ir catalysts effect the asymmetric reaction under slightly acidic conditions. A variety of chiral se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 44 publications
(62 reference statements)
0
26
0
Order By: Relevance
“…A remarkable inversion of the stereoselectivity was observed when using 3c in combination with 12 (entry 16) instead of diamines 4-7 (entries [11][12][13][14]. Although some scattered examples of inversion of stereoselectivity can be found in the literature, no general evaluation has been undertaken.…”
Section: With (Rr)-dpen 4 or (S)-daipen 7 (Entries 11 And 14)mentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable inversion of the stereoselectivity was observed when using 3c in combination with 12 (entry 16) instead of diamines 4-7 (entries [11][12][13][14]. Although some scattered examples of inversion of stereoselectivity can be found in the literature, no general evaluation has been undertaken.…”
Section: With (Rr)-dpen 4 or (S)-daipen 7 (Entries 11 And 14)mentioning
confidence: 99%
“…Although some scattered examples of inversion of stereoselectivity can be found in the literature, no general evaluation has been undertaken. [11] The reduction of other heterocycles to provide isoquinolines 16-17, benzothiophene 18, benzofuranone 19, and pyrazole 20 also resulted in high selectivities (Table 4). Complete inversion of enantioselectivity was also observed in these cases using pre-made complexes 26 and 27.…”
Section: With (Rr)-dpen 4 or (S)-daipen 7 (Entries 11 And 14)mentioning
confidence: 99%
“…This catalyst system chemoselectively afforded the corresponding chiral alcohols in almost quantitative yields and up to 99% optical yields. Since then, a number of AHs catalyzed by Ru(II) complexes, like C1 bearing chiral diphosphine, and diamine ligands for structurally diverse substrates, like alkyl-aryl ketones, heteroaromatic ketones, unsymmetrical benzophenones, aliphatic and , -unsaturated ketones, has been reported (Noyori & Ohkuma, 2001;Ohkuma, 2010). Furthermore, proper matching of a chiral ruthenium diphosphine with the correct enantiomer of diamine leads to exceptionally enantioselective catalysts, which are also highly chemoselective for C=O group vs. C=C and C≡C bonds, and tolerate many functionalities, like NO2, CF3, halogen, acetal, CO2R, NH2, NHCOR, etc.…”
Section: Ru- Rh-and Ir-catalyzed Hydrogenation and Transfer Hydrogenmentioning
confidence: 99%
“…After examining numerous chiral diamines, Noyori, Ohkuma, and their co-workers found that the most effective catalyst systems were BINAP-DPEN (DPEN = 1,2-diphenylethylenediamine) (33) and BINAP-DAIPEN (DAIPEN = 1,1-di-4-anisyl-2-isopropyl-1,2-ethylenediamine) (34) (Fig. 2) [16,17,47]. In particular, the latter catalytic system (34), which has sterically more demanding 3,5-xylyl moieties on the phosphorus atoms exhibited exceedingly high catalytic activities and enantioselectivities in the hydrogenation of a wide range of ketone substrates.…”
Section: Hydrogenation Of Simple Ketonesmentioning
confidence: 99%